Perspective on Forest Conservation: A Case Study of Community at Gana Resettlement and Integrated Development Project (GRID), Sabah, Malaysia - Hardawati Yahya; Roszehan Mohd. Idrus; Hamimah Talib; Eunice Fong (Kangwon National University, Chunchon, Korea, 2012)
This study was carried out in Gana Resettlement and Integrated Development (GRID) Project as a pioneer model for Community-Based Forest Management (CBFM) in Sabah, Malaysia. The GRID project is developed to improve community livelihood as well as to promote community involvement in CBFM and at the same time to lessen community encroachment and traditional farming practices inside the forest conservation area. The objectives of this study are: (i) to identify the dependency of local community on forest resources; (ii) to examine local community's roles in conserving forest resources and, (iii) to analyze their views on GRID project in conserving forest. Interviews were conducted with randomly selected 130 households at the GRID project using semi structured questionnaires comprising closed and open-ended questions. The study reveals that community dependency on forest resources have lessened after the resettlement of the GRID project. The community shows positive perspective on their contribution for conserving the forest resources. However, the community's willingness to contribute as well as their real contribution can be further improved. The study recommends the government to create more effective training and relevant activities to improve the livelihood of community as well as to increase their positive perception on forest conservation efforts. Further research to strengthen the relationship between local community and forest governance through forest conservation is also recommended.